Analysis of Revenue Accounting Information Systems at M98 Baby Shop Shop, Bengkulu City - Samsiah Maripah; Ahmad Soleh; Nenden Restu Hidayah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study aims to analyze the income accounting information system at M98 Baby Shop in Bengkulu City. The data collection method is the interview method. The analytical method used is descriptive analysis with a comparative type. The results show that the income accounting information system, especially cash sales at M98 Baby Shop in Bengkulu City included: related functions, documents used, accounting records used and procedures that formed the system. In the application of income accounting information systems at M98 Baby Shop in Bengkulu City, there is a suitability of related functions and a network of procedures that form the system with the theory presented by Mulyadi, because at M98 Baby Shop in Bengkulu City, there is an income process that starts from the sales process and cash transfers to the bank and there is a separation of responsibilities between functions which is in the M98 Baby Shop in Bengkulu City. For the documents used and the accounting records used, there is a difference between Mulyadi's theory and M98 Baby Shop in Bengkulu City because at M98 Baby Shop in Bengkulu City, there is no journalizing at the time of the transaction because all transactions noted t is computerized with existing programs, and the documents used are not in accordance with Mulyadi's theory because all existing documents are only related to cash sales.